Interventions and strategies to improve social support for caregivers of children with chronic diseases: An umbrella review - Yang, Jinrong; Lin, Lin; Gao, Yuqin; Wang, Weiren; Yuan, Lulu (Frontiers in Psychiatry, 2022)
Background: Social support is an important approach to improve the psychosocial health status and promote positive coping for caregivers of children with chronic diseases. Such an approach can reduce parenting stress, help resolve parenting difficulties through the use of various social support relationships. Methods: We performed an umbrella review methodology using the method of examination, analysis and synthesis of systematic reviews. A PRISMA flow diagram was used to show the search process. The Joanna Briggs Institute was used to appraise the quality of papers and a narrative synthesis was undertaken. Relevant English and Chinese systematic reviews were searched in Embase, PubMed, Web of science, OVID, CNKI, CBM, Wanfang and Cochrane Library databases, until November 2021, June 2022. Results: Out of 1,905 records, we included fourteen systematic reviews for a synthesis. Evidence to promote social support for caregivers of children with chronic diseases was identiﬁed from four key aspects: (i) Intervention contents; (ii) Intervention forms; (iii) Intervention time; and (iv) Sources of support. Conclusions: The ﬁndings of this review suggest that a combination of differing interventions, especially for early family, including the contents of parenting training or education, attitude building and resource provision, which can implement online is recommend. More extensive high-quality original researches are still needed. Impact: Sufficient social support is the welfare to promote mental health of caregivers of children with chronic diseases. In the early stage of children’s diseases, integrating different contents and forms of interventions for caregivers’ families and actively helping caregivers to identify available support resources can improve social support. The findings from this review can be used to guide caregivers of children with chronic diseases and provide evidence for healthcare professionals and social workers to carry out relevant interventions.